Slovenska književnost v srednjeevropskem prostoru in položaj drugega - Borovnik, Silvija (Slavia Centralis, 2020)
SLOVENIAN LITERATURE IN CENTRAL EUROPE IN TERMS OF ITS TREATMENT OF THE OTHER AND THE DIFFERENTThe article deals with the position of Slovenian literature in Central Europe in terms of its treatment of the Other and the Different. In the past, Slovenians lived in regions of other nation states and their status was subordinate and unacknowledged, which was also a situation experienced by other Central European peoples. In such a situation, writing in the Slovenian language meant a decision to occupy the “position of the other”, generally considered inferior and intellectually inadequate. When Slovenian literature became established, this status of difference was ascribed to German writing, for example. In contemporary times, there has been a conscious decision to recognise writers in Slovenian who write in other languagesand incorporate their work in our literary history. The Slovenian literary canon must begin to include writers with so-called dual literary and linguistic identity.
Keywords: Slovenian literature; Central Europe; bilingualism; biculturalism; interculturalism; transculturalism